Serum albumin secretion in rat milk. - Geursen, A (1987)
1. The concentration of serum albumin in rat milk, rat serum, the stomach contents of suckling rats and mammary homogenates has been measured. 2. Serum albumin in expressed milk ranges in concentration between 3.5 and 6 mg/ml and amounts to an average of 4-5 mg/100 mg total protein whereas, in the stomach contents of suckling rats, serum albumin was 3.2 mg/100 mg total protein. 3. Corresponding concentrations of a second soluble milk protein, alpha-lactalbumin, were 2.9 mg/100 mg total protein in the milk and 1.2 mg/100 mg total protein in the stomach contents. 4. Serum albumin is a major protein in mammary homogenates at 10 mg/100 mg total soluble protein and the calculated total mammary pool of albumin amounts to 110 mg/rat. 5. There was a significant negative correlation between the serum albumin concentration and the ratio of potassium to sodium ions in milk samples obtained from rats milked with varying oxytocin treatments. 6. No evidence for albumin mRNA could be detected when mammary total RNA was probed with a complementary DNA (cDNA) for rat albumin. 7. The data are consistent with albumin being a major whey protein in the rat, it being synthesized at an extramammary site and transferred to the milk space by a paracellular mechanism from an extravascular mammary pool rather than directly from the serum.